2006
DOI: 10.1136/oem.2006.027839
|View full text |Cite
|
Sign up to set email alerts
|

Hospital injury rates in relation to socioeconomic status and working conditions

Abstract: Objectives: To describe the risk of work injury by socioeconomic status (SES) in hospital workers, and to assess whether SES gradient in injury risk is explained by differences in psychosocial, ergonomic or organisational factors at work. Methods: Workforce rosters and Occupational Safety and Health Administration injury logs for a 5-year period were obtained from two hospitals in Massachusetts. Job titles were classified into five SES strata on the basis of educational requirements and responsibilities: admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…Visible minority status, language, cultural group, and immigration status are also associated with exposures to risk factors for musculoskeletal disorders and with reporting and receiving compensation for occupational disorders (46)(47)(48)(49)(50). Education and other indicators of socioeconomic status have also been linked to exposures and outcomes, and, in addition, such relationships differ according to gender (25,51). Stratifying for all of these at once is not usually possible with the sample sizes normally available.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Visible minority status, language, cultural group, and immigration status are also associated with exposures to risk factors for musculoskeletal disorders and with reporting and receiving compensation for occupational disorders (46)(47)(48)(49)(50). Education and other indicators of socioeconomic status have also been linked to exposures and outcomes, and, in addition, such relationships differ according to gender (25,51). Stratifying for all of these at once is not usually possible with the sample sizes normally available.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Overall, studies have shown that the risk of disease among nursing technicians and assistants is much greater than that of nurses, especially in terms of musculoskeletal disorders. Furthermore, the risk of occupational injuries among less qualified nursing professionals is reported to be four times higher than in the nurse category (11)(12)(13)(14)(15)(16) . A study conducted in a public hospital found that the hiring of nursing technicians and assistants was higher than for nurses, who were hired at rates below those recommended by COFEN (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Rather, rates are attenuated after adjusting for psychosocial and ergonomic workplace exposures, suggesting that workplace differences may be the true predictor 16,17 . Stress, fatigue, burnout and frustration play a crucial role in occupational injury, with job strain demonstrated to be the most important predictor of functional health status 18 .…”
Section: Hospital Risk Factorsmentioning
confidence: 99%
“…The majority of overexertion injuries are the result of cumulative trauma and can manifest as symptoms of a poorly designed workplace, particularly considering an environment not conducive to safe patient handling tasks. No places to rest, hazardous equipment and noise levels have been identified as physical environment characteristics that lead to unsafe situations and dangers 16 . In one study, nurses in both high and low claim rate hospitals ranked the physical work environment as the second most important contributor of musculoskeletal injury, behind workload…”
Section: All Authors Contributed To Conception and Design Manuscri Tmentioning
confidence: 99%